2016
DOI: 10.1177/1934578x1601101204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Evaluation of Artemisinin–triazole Hybrids

Abstract: Dihydroartemisinin was converted to its corresponding alkyne-functionalized esters, which were subsequently deployed as substrates for a 'click' chemistrymediated coupling with 3'-azido-3'-deoxythydimine (AZT) to furnish novel triazole-artesunate-AZT hybrid compounds. Moreover, various substituted triazole-artemisinin hybrids were synthesized based on 'click' chemistry between propargyl-substituted derivatives and artemisinin containing a 2-hydroxypropane unit. Fourteen new hybrids were thus successfully prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Structure activity relationship (SAR) studies indicated that the spacer between triazole-artiartemisinin and triazole-coumarin as well as the substituents on the coumarin were critical to the selective inhibitory activity. Artemisinin-azidothymidine hybrid b10 (IC 50 = 16.5 μ M) could exert more potent antiproliferative activity than artesunate (IC 50 = 78.5 μ M) against KB cancer cells ( Tien et al, 2016 ), indicating the azidothymidine moiety plays a key role in the increased activity. In addition, SAR studies showed that hybrids with ester triazole-linker could exert more potent antiproliferative activity than hybrids with amide triazole-linker.…”
Section: Click Chemistry-based Modification Of Terpenoidsmentioning
confidence: 99%
“…Structure activity relationship (SAR) studies indicated that the spacer between triazole-artiartemisinin and triazole-coumarin as well as the substituents on the coumarin were critical to the selective inhibitory activity. Artemisinin-azidothymidine hybrid b10 (IC 50 = 16.5 μ M) could exert more potent antiproliferative activity than artesunate (IC 50 = 78.5 μ M) against KB cancer cells ( Tien et al, 2016 ), indicating the azidothymidine moiety plays a key role in the increased activity. In addition, SAR studies showed that hybrids with ester triazole-linker could exert more potent antiproliferative activity than hybrids with amide triazole-linker.…”
Section: Click Chemistry-based Modification Of Terpenoidsmentioning
confidence: 99%